Anurans trophic dynamic and guild structure in tropical dry forests of the Caribbean region of Colombia (2021)
Studies on the exploitation of trophic resources allow to establish interactions between predators and predator-prey, and this dynamic can present fl uctuations over time and space. We analysed stomach contents of 19 anuran species from tropical dry forests of Colombia, quantifi ed the overlap between species and identifi ed anuran trophic guilds. Most of the species were generalists in diet (89.5%), some with strong prey dominance and only two species were classifi ed as specialists. Two anurans guilds were identifi ed according to diet structure and habitat use: “ground foraging anurans, consuming Formicidae and Isoptera” and “arboreal ‘sit-and-wait’ predators, primarily consuming arachnids”. A considerable number of species did not clearly group in community trophic structure analysis. The level of taxonomic resolution with that preys are worked affects analysis of trophic niches segregation when analyzing regional and local patterns. Anuran species of tropical dry forest in the Colombian Caribbean display trophic resources partitioning at the level of species and/or morphospecies, as a mechanism of coexistence.